Perceived effectiveness of internationalization support services: A configurational approach of the interplay between provided knowledge types and managers’ inherited knowledge - Bérard, Céline; Séville, Martine; Martinot-Lagarde, Armance (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2023)
Studies on the effectiveness of internationalization support services (ISSs) tend to neglect the role of managerial cognition. Adopting a configurational approach, we thus focus on the interplay between the types of knowledge provided by ISSs and the managers’ inherited knowledge to explain their perceived effectiveness. Results demonstrate that the acquisition of network knowledge from ISSs is a necessary condition, but not sufficient, to perceive them as effective. The need to acquire diversified knowledge through these services also depends on the managers’ country-specific or non-specific international experience.